Assessments of Sand Dune Ecosystem Service Potential from Son Tra (Da Nang) to Tam Ky (Quang Nam) - Bac, Dang Kinh; Bao, Dang Văn; Thanh Hang, Dang Thi; Cuong, Ngo Chi (VNU Journal of Science: Earth and Environmental Sciences, 2020)
The coastal area in the Son Tra – Tam Ky region have various kinds of sand dunes: (1) embryo dunes; (2) foredunes; (3) yellow dunes; (4) gray dunes; (5) white dunes; (6) brown dunes. These sand dunes play an important role in maintaining biodiversity, minimizing the damage of natural hazards and tourism development. In last decade, the sand dunes in Son Tra (Da Nang) - Tam Ky (Quang Nam) is strongly influenced by urbanization and tourism development. Different resorts have been built along the beaches, narrowing protective forests on the sand dunes. It does not only reduce the value of cultural ecosystem services; but also, the ability to regulate natural disasters and air pollution. Therefore, the study aims to assess the unbalance in sand dune ecosystems service supply in Son Tra - Tam Ky area. Methods used in the study include: remote sensing and GIS, collecting statistics and specialist interviews. The results showed a clear differentiation in the potential of the ecosystem services in different sand dune types. Lastly, the study analyzed the values of sand dune ecosystem services in Son Tra - Cua Dai part; to assess differences in planning and development policies between the coastal zones of Quang Nam and Da Nang.